The train - Callaghan, Jodie, 1984- (Second Story Press, 2020)
"A fiction picture book about residential schools. Author Jodie Callaghan worked as a journalist at the time of the Canadian government's apology for the residential school system. She took inspiration for this book from her conversations with survivors--including her own grandmother's experience at Indian day school, and memories shared with her by a man she interviewed by the train tracks that transported children to residential school in Shubenacadie, Nova Scotia. Jodie's story for The Train was first recognized as the winner of the Mi'gmaq Writer's Award in 2009, a contest organized by the Mi'gmawei Mawiomi Secretariat to encourage and develop Mi'gmaq storytellers."--